The Comparison of Stereotactic Body Radiation Therapy and Intensity-Modulated Radiation Therapy for Prostate Cancer by NCCN Risk Groups - Ricco, Anthony; Manahan, Genevieve; Lanciano, Rachelle; Hanlon, Alexandra; Yang, Jun; Arrigo, Stephen; Lamond, John; Feng, Jing; Mooreville, Michael; Garber, Bruce; Brady, Luther (Frontiers in Oncology, 2016)
Objectives The primary objective of this study is to compare freedom from biochemical failure (FFBF) between stereotactic body radiation therapy (SBRT) and intensity-modulated radiation therapy (IMRT) for patients with organ confined prostate cancer treated between 2007 through 2012 utilizing the 2015 National Comprehensive Cancer Network (NCCN) risk stratification guidelines. A secondary objective is to compare our updated toxicity at last follow-up compared with pretreatment with respect to bowel, bladder, sexual functioning, and need for invasive procedures between the two groups. Methods We retrospectively reviewed 270 consecutive men treated with either SBRT (n = 150) or IMRT (n = 120) at a community hospital with two distinct radiation departments and referral patterns. Charts were reviewed for pretreatment and treatment factors including race, age, clinical T stage, initial PSA, Gleason score, use of androgen deprivation therapy, treatment with SBRT vs. IMRT, as well as stratification by 2015 NCCN guidelines. Kaplan–Meier (KM) methodology was used to estimate FFBF, with statistical comparisons accomplished using log rank tests. Multivariable Cox proportional hazard modeling was used to establish independent factors prognostic of biochemical failure. Descriptive statistics were used to describe toxicity graded by a modified Radiation Therapy Oncology Group (RTOG) late radiation morbidity scoring system. Results Significant prognostic factors in univariate analysis for FFBF included NCCN risk groups (p = 0.0032), grade (p = 0.019), and PSA (p = 0.008). There was no significant difference in FFBF between SBRT vs. IMRT (p = 0.46) with 6-year actuarial FFBF of 91.9% for SBRT and 88.9% for IMRT. Multivariable analysis revealed only the NCCN risk stratification to be significant predictor for FFBF (p = 0.04). Four-year actuarial FFBF by NCCN risk stratification was 100% very low risk, 100% low risk, 96.5% intermediate risk, 94.5% high risk, and 72.7% very high risk. There were no grade 3 gastrointestinal or genitourinary toxicities for either SBRT or IMRT at last follow-up. Conclusion No significant difference in FFBF was found between SBRT and IMRT for organ confined prostate cancer in multivariable analysis within this retrospective data set. Overall toxicity was low. The 2015 NCCN risk stratification was validated in this population and was the only significant factor for FFBF in multivariable analysis.